PERAN STRATEGIS GURU PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER GENERASI Z DI ERA DIGITAL - Yoges Mahendra Saragih (Sekolah Tinggi Teologi Mawar Saron Lampung, 2025)
Generation Z, or Zoomers, is often touted as a tech-savvy generation. However, there are many aspects to consider regarding their proficiency with technology. The potential they possess is expected to help them grow and easily keep up with the times, rather than leading them into the negative impacts of technology. This article will delve deeper into the important role of educators or Christian Religious Education (CRE) teachers in shaping the character of Generation Z. Teachers have a significant influence in the school environment, with authority and power being substantial because they can interact directly with students. Through this, teachers can provide character and moral education. The method used is qualitative, with data drawn from literature studies. The findings of this study are expected to offer insights into the vital role of teachers as role models in Christian Religious Education and how they can shape the character of Generation Z students through teaching in schools.